TikTok Framing Analysis: @soloposofficial In the Conflict Involving Brimob Colliding with a Gojek - Ananda Rizqi Ramadhan; Nawiroh Vera (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The "Brimob crashes into online motorcycle taxi" incident that occurred on August 28, 2025, garnered widespread attention on social media and revealed differing narratives between public media and the police institution. Social media has become important news in shaping public perception thru the meanings and symbolism present in the media. This research aims to determine how the @soloposofficial account frames the event in video uploads on TikTok. The research method used is descriptive qualitative analysis with Zhongdang Pan and Gerald M. Kosicki's framing analysis, using the main structures in analyzing media, namely: syntactic structure (information and narrative arrangement in the video), script structure (event delivery flow), thematic structure (patterns of meaning and main issues), and rhetorical structure (language style, visuals, and message symbols). The research results show that the @soloposofficial account frames events as a social conflict issue. With dramatic aspects, video searches at the scene, and public response. Not all responses on that platform convey a uniform perspective on the current hot topic; each account actually demonstrates a different way of using digital language to create meaning. It's clear how each party's communicative approach reveals its own goals some want to clarify, while others are more focused on protecting the institution's reputation. From this, it's clear that online tactics are not just a tool for disseminating information, but a form of strategic interaction influenced by the context of the content. Keywords: Framing Analysis, Brimob, TikTok, Social Conflict, Digital Communication.